THE POLITICAL CONSPIRACY IN BRYAN SINGER'S VALKRYIE MOVIE (2008): A SOCIOLOGICAL APPROACH - EFENDI, MAHFUT (2010)
This study is aimed to show the political conspiracy in Valkryie movie by using sociological approach. It is done by establishing two objectives: the first is analyzing the movie based on its structural elements and the second is analyzing the movie based on the sociological approach. This research is qualitative research. Type of data of the study is text and image taken from two data sources: primary and secondary. The primary data source is the Valkryie movie directed by Bryan Singer released in 2008. While the secondary data sources are other materials taken from books, journals, and internet related to the study. Both data are collected through library research and analyzed by descriptive analysis. The study comes to the following conclusions. First, based on the structural analysis of each elements, it shows that the character and characterization, casting, plot, setting, point of view, theme, mise en scene, cinematography, sound, and editing are related to each other and form the unity into good quality of a movie. Second, based on the sociological analysis, there is close relation between the movie production and the social reality underlying it, such as the global issues of conspiracy in a government. This movie also criticizes the assassination of leader to drop a cruel government for people affair.